2012
DOI: 10.1111/j.1365-2052.2012.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset progressive retinal atrophy in the Gordon and Irish Setter breeds is associated with a frameshift mutation in C2orf71

Abstract: Progressive retinal atrophy (PRA) in dogs is characterised by the degeneration of the photoreceptor cells of the retina, resulting in vision loss and eventually complete blindness. The condition affects more than 100 dog breeds and is known to be genetically heterogeneous between breeds. Around 14 mutations have now been identified that are associated with PRA in around 49 breeds, but for the majority of breeds the mutation(s) responsible have yet to be identified. Using genome-wide association with 16 Gordon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…Novel uncharacterised proteins are still being discovered to play a role in such processes, such as C8orf37, a ciliary protein which is mutated in CORD and RP 232 and C2orf71, a ciliary protein mutated in RP in humans and progressive retinal atrophy in several breeds of dog. 233,234 While our understanding of primary cilia and specialized sensory cilia such as the photoreceptor has advanced greatly in the past two decades, there still remains much to discover. With the ever-increasing power and affordability of genetic sequencing technologies, there are now unprecedented opportunities for rapid gene discovery in this group of retinal conditions, providing further insights into disease mechanism.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…Novel uncharacterised proteins are still being discovered to play a role in such processes, such as C8orf37, a ciliary protein which is mutated in CORD and RP 232 and C2orf71, a ciliary protein mutated in RP in humans and progressive retinal atrophy in several breeds of dog. 233,234 While our understanding of primary cilia and specialized sensory cilia such as the photoreceptor has advanced greatly in the past two decades, there still remains much to discover. With the ever-increasing power and affordability of genetic sequencing technologies, there are now unprecedented opportunities for rapid gene discovery in this group of retinal conditions, providing further insights into disease mechanism.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…21 The rcd4 mutation is a duplication of a C in exon 1 of the gene. The normal allele has a run of 6 Cs and the mutant allele 7 Cs (c.3149_3150dupC).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary unpublished studies on the MSU samples had shown an association with the previously reported mutation in the canine equivalent of C2ORF71 (chromosome 2 open reading frame 71: the canine homolog is on canine chromosome 17 and referred to as c17h2orf71). 21 Therefore, dogs were tested for this mutation as well as the prcd mutation which has been described across multiple breeds of dog. 17 To screen for the rcd4 mutation, a one base-pair insertion in c17h2orf71, about 50 ng of genomic DNA was used to PCR amplify a fragment of 670/671 basepairs encompassing the duplication site (forward primer 5 0 -CACACATGTGGACAGCACAG-3 0 and reverse primer 5 0 -AAGCGGTCCTTCTGATGAAA-3 0 designed using Primer3 (http://bioinfo.ut.ee/primer3-0.4.0/)).…”
Section: Dna Testingmentioning
confidence: 99%
“…Retinal disorders can be categorized in various ways and the way in which they have been Cone-rod dystrophy CRD3 ADAM9 Glen of Imaal terrier [53,54] Primary open angle glaucoma POAG ADAMTS10 Beagle [147] Primary lens luxation PLL ADAMTS17 Multiple, mainly terrier breeds [129,132] Rod cone degeneration RCD4 C2orf71 Gordon Setter, Irish Setter, Tibetan Terrier [30] Generalised progressive retinal atrophy gPRA CCDC66 Schappendoes [28] Progressive retinal atrophy PRA CNGB1 Papillon [15,17] Cone degeneration CD CNGB3 Alaskan malamute [68] Cone degeneration CD CNGB3 German shorthaired pointer [69] Dwarfism with retinal dysplasia (oculoskeletal dysplasia) DRD2 (OSD2) COL9A2 Samoyed [90] Dwarfism with retinal dysplasia (oculoskeletal dysplasia) DRD1 (OSD1) COL9A3 Labrador retriever [90] Hereditary cataract HC, EHC HSF4 Staffordshire bull terrier, Boston terrier, French bulldog [103] Hereditary cataract HC HSF4 Australian Shepherd [107] Collie eye anomaly CEA NHEJ1 Collies [91] Cone-rod dystrophy NPHP4 Standard wirehaired dachshund [49] Photoreceptor dysplasia PD PDC Miniature schnauzer [13] Rod cone dysplasia RCD1 PDE6B Irish setter [2] Rod cone dysplasia RCD1 PDE6B Sloughi [3] Rod cone dysplasia RCD3 PDE6A Cardigan Welsh corgi [4] Progressive rod-cone degeneration PRCD PRCD Multiple breeds [23] Rod cone dysplasia RCD2 RD3 Collie [7] Autosomal dominant progressive retinal atrophy ADPRA RHO English mastiff [24] Congenital stationary night blindness CSNB RPE65 Briard [58,59] X-linked progressive retinal atrophy XLPRA2 RPGR Mixed breed dogs [18] X-linked progressive retinal atrophy XLPRA1 RPGR Siberian Husky, Samoyed [18] Cone-rod dystrophy CORD1 (CRD4) RPGRIP Dachshunds [38] Early retinal degeneration ERD STK38L Norwegian elkhound [11] Canine multifocal retinopathy CMR1…”
Section: Diseases Of the Retinamentioning
confidence: 99%
“…The function of C2orf71 remains unknown, but it is important for retinal development and function and has previously been associated with autosomal recessive retinitis pigmentosa in humans [31][32][33][34]. The form of PRA associated with the mutation in C2orf71 has been termed RCD4, for rod-cone degeneration 4, to distinguish it from other forms of rod-cone degeneration [30]. The mutation has also been found in Tibetan Terriers affected with PRA (Mellersh and Downs, unpublished).…”
Section: Progressive Retinal Atrophymentioning
confidence: 99%